2004
DOI: 10.11150/kansenshogakuzasshi1970.78.717
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of ^|^beta;-lactam Antibiotic Induced Vancomycin-resistant MRSA from Clinical Isolated MRSA

Abstract: Recently, beta-lactam antibiotic induced vancomycin-resistant MRSA (BIVR) has been reported increasingly in Japan. Between 1998 and 2002, we tried to detect BIVR from 500 strains of MRSA in a cancer hospital. And the difference of the detection rate under condition of pre-culture with or without ceftizoxime was compared. The detection rate of BIVR under condition of pre-culture with 1.0 mg/L of ceftizoxime was 20.4% (102/500), and without ceftizoxime was 9% (45/500). That of preculture with 1.0 mg/L of ceftizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…4 However, another problem arose, with a new type of vancomycin-resistant MRSA, which emerged with the simultaneous use of vancomycin and β-lactam antibiotics; this organism exhibited elevated vancomycin resistance and has been designated as β-lactam-induced vancomycin-resistant MRSA (BIVR). [5][6][7][8][9] A model study showed that 100% of BIVR-infected mice treated with vancomycin alone survived, while only 20% of the infected mice treated with vancomycin and ceftizoxime survived. 10 Two cases of BIVR emergence were reported clinically, in a burn patient and a renal failure patient; both were initially treated with a combination of vancomycin and imipenem.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, another problem arose, with a new type of vancomycin-resistant MRSA, which emerged with the simultaneous use of vancomycin and β-lactam antibiotics; this organism exhibited elevated vancomycin resistance and has been designated as β-lactam-induced vancomycin-resistant MRSA (BIVR). [5][6][7][8][9] A model study showed that 100% of BIVR-infected mice treated with vancomycin alone survived, while only 20% of the infected mice treated with vancomycin and ceftizoxime survived. 10 Two cases of BIVR emergence were reported clinically, in a burn patient and a renal failure patient; both were initially treated with a combination of vancomycin and imipenem.…”
Section: Introductionmentioning
confidence: 99%
“…The infection rates were in 6 patients (2.8%), 7 patients (3.5%) and 3 patients (1.4%) respectively, and it was observed Clinical success in 86 (68.3%) of the 126 patients included in the efficacy population. The monotherapy and combination subgroups had similar proportions of patients with success (69.7%, 64.9%, respectively), where the treatment period was 2 days (quadruple range of 1.5 to 4 days) for monotherapy, in 3 days (Quadruple range from 1.5 to 5 days) for combination therapy, where the results showed that cefazolin is effective for monotherapy or combination therapy (25,26,31).…”
Section: Countries Of the Worldmentioning
confidence: 86%
“…S.aureus has been observed mainly in neonatal sepsis, skin and soft tissue infections, pneumonia, arthritis, osteoarthritis, endocarditis and postoperative sepsis. Multidose bacteria were encountered in all hospitals studied, penicillin resistance rates ranged from 40% to approximately 100%, while methicillin resistance rates of up to 52% have been reported in several hospitals (26,33).…”
Section: Countries Of the Worldmentioning
confidence: 95%
See 1 more Smart Citation